Investigation of the determinants of alcohol use among women in Oshikoto region, Namibia - Rebekka N. Netope; Emma M. Nghitanwa; Tuwilika Endjala (AOSIS, 2023)
Background: Alcohol abuse is one of the world's main public health issues. Alcohol use is growing among African women, and it has become an underlying factor in women's health risk profiles. Objective: The purpose of this study is to investigate the factors that influence women's alcohol consumption in the Oshikoto Region. Materials and Methods: The study used a quantitative research method with a cross-sectional, analytical design. Data were gathered using interview-led questionnaires from 121 women aged 18-49 years at two state hospitals in the Oshikoto region's two selected constituencies. The Statistical Package for the Social Sciences, version 26, was used to evaluate the data. Results:  The subjects' median age was 33 years old. The bulk of the participants, 84 (69.4%), resided in rural areas. 49 (40.5%) of the participants were unmarried, and the majority (62%) had children. According to the results, 64 (52.89%) of respondents use alcohol to cope with their problems on occasion. When they are anxious, approximately 56 (46.28%) of the respondents use alcohol to relax and ignore their problems. In the univariable log-binomial regression analysis, a family history of alcohol use (p-value 0.019), peer pressure (p-value 0.004), and spending the majority of time at Cuca shops (p-value 0.000) were all linked with an increased risk of harmful alcohol use. Conclusion: Identifying the determinants of alcohol use may aid in the creation of recommendations for preventative measures and alcohol awareness programs.